O DIREITO FUNDAMENTAL AO ESTABELECIMENTO DISTINTO PARA MULHERES QUE CUMPREM PENA PRIVATIVA DE LIBERDADE EM REGIME FECHADO - Sá, Luana Rodrigues Meneses de (2022)
This dissertation is part of the Research Line "Fundamental Rights, Democracy and Sustainable Development''. The problem of the dissertation is the question of what are the main obstacles to the realization of the right to a separate establishment for serving time in prison from a gender perspective. The general objective is to analyze the main obstacles in the right of female criminal execution that make it impossible to realize the fundamental right to a separate establishment for women serving time in a closed regime. The specific objectives are to work the specialized literature review to analyze the theoretical and methodological contributions in the scope of the right of penal execution, integrating the perspective of gender in the legal doctrine; to investigate the legal propositions, the barriers, and the gaps that make the materialization of the right to the distinct penal establishment unfeasible, as well as to identify the process of specification of the fundamental rights and the public policies of the women who serve their prison sentences in closed regime; and to investigate the legal-institutional dimension of the National Policy of Attention to Women in Situation of Freedom Deprivation and Egresses from the Prison System (PNAMPE), and the State Plan of Attention to Women in Situation of Freedom Deprivation and Egresses from the Prison System of Mato Grosso do Sul, with emphasis on data from women incarcerated in the Penal Establishment Sister Irma Zorzi, in Campo Grande/MS. For this, we used the techniques of bibliographic research, bibliographic review of specialized literature aiming to the mapping of proposals for legal solutions and document analysis, focusing on data from the DEPEN and AGEPEN/MS penitentiary survey, institutional data on public policies of attention to incarcerated women and prison administration, it was also used the resource of the Law of Access to Information (LAI) for knowledge of the legal dimension of the PNAMPE. This was interpreted in the light of the theoretical referential of Feminist Critical Criminology. The conclusion points out the importance of the effective functioning of gender public policies, especially PNAMPE, and the role of law operators to intervene in its monitoring, pondering that the state omission entails punitive increases and hinders the realization of fundamental rights of incarcerated women. The aspects of material and immaterial conditions of imprisonment, such as overcrowding and penal services devoid of attention to gender, are in conflict with the conception of separate establishments for women, consequently, the recognition of the process of decarceration is observed as a prerequisite for the strict respect of the fundamental right to separate establishments from the gender perspective, given that the implications of its non-compliance result in gender inequality. It is inadmissible that the existential minimum figure as a justification for the non-fulfillment of the state duty to implement broad public policies or that the reflections of the special relations of subjection remain to the detriment of dignified female criminal execution.